Contribuição da psicoterapia de grupo para o estudo de pacientes com disfunção temporomandibular - Eberlein, Marina Cardoso Smith [UNIFESP] (2019)
Objectives: reflect about the experience of group brief psychotherapy impact applied on three sets of patients from Temporomandibular Disorder Clinic at the Hospital São Paulo (UNIFESP) and to examine how such approach can promote raise of their emotional experiences awareness advancing beyond their body expressions. Analyze how this approach can increase the symbolic expression of the affection and which are the most recurrent themes brought into the three groups. Methods: the investigation design is a clinical qualitative retrospective research with three separate brief psychotherapy groups, each one performed with 12 therapy sessions, in a psychodynamic theoretical approach, totaling 18 patients (Group I with 6 participants, Group II with 8 and Group III with 4). The participants were selected by a personal psychological interview after a dentist referral. The sessions were documented and subsequently examined by the most significant and frequent thematic axes. Each group and each individual therapeutic process were analyzed. Results: The author observed a female gender prevalence in 8:1 in relation to male. The age group found was 36 to 77 years, most were professionally inactive (15), predominance of traumatic life stories with losses, abandonments, violence, poverty, fragility of reliable links. It was observed some varied group dynamics, from more structured and organized groups, where a reliable link was built, to less structured and disorganized experiences, where no link was established. It was observed a plurality of individual trajectories, without a homogeneous profile. The majority showed interest to continue the self-knowledge process. The most frequently topics were subjects related to the narcissistic issues like non-differentiation between self and not-self, the trauma, the violence, aggression and the body expression of suffering. Conclusion: The therapeutic group as an embracing model and tie stimulator could develop an experience of psychic integration and differentiation to patients with pain.